(untitled) (Samarra Journal of Pure and Applied Science, 2026)
Schiff base [L3] ((E)-1,2-diphenyl-2-(pyridin-2-ylimino)ethan-1-ol) was synthesized in a 1:1 ratio from benzoin and 2-hydrazinopyridine, along with its Co(II), Ni(II), Cu(II), and Zn(II) complexes. synthesized compounds were characterized by ¹H-NMR, ¹³C-NMR, FT-IR, Uv-Vis and molar conductivity measurements. Additionally, Cu(II) and Ni(II) nanocomplexes were prepared using Pulsed Laser Ablation in Liquid (PLAL) and characterized via FESEM, EDX, and XRD. Their antioxidant activities were evaluated using IC50 values, compared against standard antioxidants and their bulk counterparts, while molecular docking studies explored binding interactions with VEGFR2—a key target in liver and kidney cancer treatments due to its role in angiog enesis. Furthermore, Density Functional Theory (DFT) calculations were carried out at the B3LYP level using the 6-311G++(d,p) basis set to analyze the electronic properties of the compounds